Communication Modeling for Wide-Area Relay Protection Based on IEC 61850 - GuoYan Chen; Xianggen Yin; Kai Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Wide-area communication system is the information exchange supporting platform for wide-area relay protection (WARP), which includes not only visible physical communication equipment and links, but also communication protocols and other upper communication services. WARP communication had become an important issue in WARP practical applications, but it has not been described in IEC 61850 standard. To solve this issue, this paper firstly presents the general steps of WARP modeling according to the layer upon layer modeling methods of the IEC 61850 standard, then proposes a tree structure model of master station and affiliate stations with information interaction model between master station and affiliate stations following IEC 61850 by taking a 220kV smart substation and WARP algorithm based on fault voltage distribution for example, finally establishes a communication model of WARP that includes client/server transfer model, electrical value transmission model and logical status variables transmission model. The fundamental purpose of constructing the communication model is to implement the interoperability between WARP−IED (WARP−Intelligent Electronic Devices) and other IEDs in a smart substation. DOI:http://dx.doi.org/10.11591/telkomnika.v10i7.1562